Leadership Model of Kyai Based on Four Basic Consensus of The Nation in Islamic Boarding Schools in The West Kalimantan-Malaysia Border - Misdah Misdah (Didaktika Religia, 2020)
This research aims to reveal and analyze the function of Islamic boarding schools (Ponoka Pesantren) on the border of West Kalimantan-Malaysia. The Author Will analyze the awareness of the priest/leader (Kyai) of Islamic boarding schools (Ponoka Pesantren) in developing the spirit of nationalism in the region. And to find a Kyai leadership model design based on 4 (four) National Basic Consensus in the border region of West Kalimantan-Malaysia. This type of research used is qualitative research with a case study approach. The subjects of the study are 2 Kyai, 4 Ustadz, 4 Madrasah Heads, 4 students, and 4 community leaders. The conclusions in this research are as follows; (1) the functions of Islamic boarding schools in the border region of West Kalimantan-Malaysia are boarding schools as Preaching/da'wah institutions, educational institutions, and social institutions. (2) Kyai's awareness in developing the spirit of nationalism in Islamic boarding schools in the border region of West Kalimantan-Malaysia is still relatively weak. The lack of maximum understanding of students and other residents of the Ponoka Pesantren about the national values and the lack of empowerment in the community of the Ponoka Pesantren environment in such activities to strengthening national values, such as the values of Pancasila, the 1945 Constitution, United Indonesia (NKRI), and Unity in Diversity are indicating the weakness. This is because the Kyai is still very focusing on carrying out the function of the Ponoka Pesantren as an educational institution and only preaching. (3) The design of the Kyai leadership model based on four basic consensuses of the nation in Islamic boarding schools in the border region of West Kalimantan-Malaysia is can be seen in the leadership model design diagram that researchers found.